Studying speaking to inform second language learning - Boxer, Diana, 1948-; Cohen, Andrew D. (Second language acquisition, 2004)
In a series of studies specially written for this book, "Studying Speaking to Inform Second Language Learning" offers the applied linguist research on spoken interaction in second and foreign languages and provides insights as to how findings from each of these studies may inform language pedagogy.